the effect of 23- valent pneumococcal polysaccharide vaccine on pharyngeal colonization in healthy children under 5 years of age - Rasheed, Ahmed M.; Matloob, Sami (Journal of the Faculty of Medicine Baghdad, 2007)
Background: streptococcal pneumonia is one of the most common pathogens that cause otolaryngological disease.